A lupa caleidoscópica: o híbrido policial-histórico em Agosto, de Rubem Fonseca, e Santa Evita, de Tomáz Eloy Martínez - Faraco, Mariana Bittencourt (2011)
This study discusses the effect of hybridization of the historical and the detective novels approaches from the perspective of Latin America (contemporary literature). Emerged in Europe in the 19th century, these two novel subgenres has achieved a prominent position in the literary scene. Since its genesis, both historical and detective novels deal with the question of the search for truth. The objective of this study is to detect how the enigma element, when combined with a historical narrative, reorganizes the belief in the official version of historical events. This study does a comparative analysis of two novels: Agosto, written by the Brazilian Rubem Fonseca, and Santa Evita, written by the Argentinian Tomás Eloy Martinez. Written in the 90's, both noveis look back to the 50's historical events and characters. The research recovers the criticism of both Fonseca and Martinez work, and then examines the long and traditional uneasy relations between literature and history, from Aristotle to Linda Hutcheon's historiographic metafiction. By addressing the origins and transformations of both historical and detective novels, this dissertation shows the evolutions of the subgenres and also puts into dialogue current studies of the hybrid detective-historical novel. The analysis of Agosto and~ Santa Evita, following the methodology of Comparative Literature, focuses specially on the different ways how both novels are constructed. The results demonstrate that the enigma element, when inserted into a historical narrative, contributes to a destabilization of the official report, through a multifaceted view. However, each author's different narrative strategies reveal distinct effects of this destabilization which are discussed in the present study